(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
A particular nation’s position and place in the world community does not depend on its large number or small number. On the contrary, the ability to show national characteristics, the deep understanding of the rights of the representatives of the nation, not to be materially and morally dependent on other nations, and to exist independently determines its status in the international arena.